2023
DOI: 10.1038/s41598-023-35376-1
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory mechanisms of reduced interhemispheric EEG connectivity during sleep in patients with apnea

Abstract: We performed a mathematical analysis of functional connectivity in electroencephalography (EEG) of patients with obstructive sleep apnea (OSA) (N = 10; age: 52.8 ± 13 years; median age: 49 years; male/female ratio: 7/3), compared with a group of apparently healthy participants (N = 15; age: 51.5 ± 29.5 years; median age: 42 years; male/female ratio: 8/7), based on the calculation of wavelet bicoherence from nighttime polysomnograms. Having observed the previously known phenomenon of interhemispheric synchroniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Another study performed the mathematical analysis of functional connectivity in the EEG of patients with OSA and healthy subjects by calculating wavelet bicoherence from nighttime polysomnograms. After observing the interhemispheric synchronization deterioration, this study demonstrated that high-frequency EEG activity includes a compensatory increase in intrahemispheric connection and a modest increase in the connectivity of the central and occipital lobes 14 . OSA has been linked to structural brain changes in areas related to memory and Alzheimer's disease, and a recent study showed that OSA is becoming more widely acknowledged as a risk factor for cognitive decline.…”
Section: Introductionmentioning
confidence: 85%
“…Another study performed the mathematical analysis of functional connectivity in the EEG of patients with OSA and healthy subjects by calculating wavelet bicoherence from nighttime polysomnograms. After observing the interhemispheric synchronization deterioration, this study demonstrated that high-frequency EEG activity includes a compensatory increase in intrahemispheric connection and a modest increase in the connectivity of the central and occipital lobes 14 . OSA has been linked to structural brain changes in areas related to memory and Alzheimer's disease, and a recent study showed that OSA is becoming more widely acknowledged as a risk factor for cognitive decline.…”
Section: Introductionmentioning
confidence: 85%